1964
DOI: 10.1111/j.1365-2621.1964.tb01730.x
|View full text |Cite
|
Sign up to set email alerts
|

Tocopherol Distribution in Milk Fractions and Its Relation to Antioxidant Activitya

Abstract: SUMMARY Studies were made of the distribution of tocopherol between the lipid in the fat globule membrane and inside the milk fat globule, and the relation of that distribution to the loss of tocopherol during lipid oxidation. Two fractionation procedures were used, one based on churning of cream, the other on washing cream by repeated dilution with sucrose‐saline solution and separation, followed by treatment with sodium deoxycholate. The tocopherol concentration was at least three times higher in the lipid o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 13 publications
1
23
0
Order By: Relevance
“…(Erickson et al 1964). The amount of a-tocopherol (vitamin E) associated with the membrane is considered to be the main determinant of the oxidative stability of the milk (Erickson et al 1964). …”
mentioning
confidence: 99%
“…(Erickson et al 1964). The amount of a-tocopherol (vitamin E) associated with the membrane is considered to be the main determinant of the oxidative stability of the milk (Erickson et al 1964). …”
mentioning
confidence: 99%
“…Alternatively, MFGM can directly be released from washed cream by the use of polar aprotic solvents [Bingham & Malin, 1992;Dapper et al, 1987], bile salts [Erickson et al, 1964;Snow et al, 1980], or nonionic detergents [Patton, 1982]; in addition these authors reported that direct extraction normally results in a lower yield, and a certain difference in composition depending on the concentration of the applied chemicals, the time and temperatures of extraction.…”
Section: Isolation Of Mfgm From Milkmentioning
confidence: 99%
“…Only 4% of phospholipids compared with 16% of the MFGM proteins were lost during the washing process [Anderson & Brooker, 1975]. Washing also causes losses of tocopherol, an antioxidant in the MFGM [Erickson et al, 1964].…”
Section: Milkmentioning
confidence: 99%
See 2 more Smart Citations